El primer dia de escuela - Oxenbury, Helen; Dauer, Herminia (Barcelona : Juventud, 1983)
A little girl is not looking forward to her first day at nursery school until she makes friends with another new girl.
Translation of: First day of school.
Keywords: Nursery schools -- Fiction; Friendship -- Fiction; Spanish language materials -- Juvenile fiction; Picture books